How would you solve for x when you have the problem: 2(x+1)=6(x-3).

### 1 Answer | Add Yours

We use Distributive property on both sides. a(b + c) = a*b + a*c.

`2*x + 2*1 = 6*x + 6*-3`

`2x + 2 = 6x - 18`

Put all the terms with "x" on left side, and all the other terms on right side.

Subtract both sides by 6x.

`2x - 6x + 2 = -18`

Combine like terms.

`-4x + 2 = -18`

Subtract both sides by 2.

`-4x = -20`

Divide both sides by -4.

`x = 5`

THerefore,** x = 5**.

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes